2023
DOI: 10.3390/pharmaceutics15030893
|View full text |Cite
|
Sign up to set email alerts
|

Recent Preclinical and Clinical Progress in Liposomal Doxorubicin

Abstract: Doxorubicin (DOX) is a potent anti-cancer agent that has garnered great interest in research due to its high efficacy despite dose-limiting toxicities. Several strategies have been exploited to enhance the efficacy and safety profile of DOX. Liposomes are the most established approach. Despite the improvement in safety properties of liposomal encapsulated DOX (in Doxil and Myocet), the efficacy is not superior to conventional DOX. Functionalized (targeted) liposomes present a more effective system to deliver D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 144 publications
0
24
0
Order By: Relevance
“…While we utilized a novel sustained-release formulation of phenylephrine, we used standard melphalan (aqueous solution) for intratumoral chemotherapeutic injections. Others have shown that a sustained-release liposomal formulation of melphalan enhanced the antitumor effects in preclinical animal models. Our group and others have also published on the beneficial effects of other sustained-release liposomal chemotherapies. , Furthermore, liposomal doxorubicin is an effective and approved drug for different human cancers, including breast and ovarian cancer . Thus, combining sustained-release liposomal formulations of intratumoral chemotherapy may likely have an additional effect on antitumor responses when used in combination with our local dynamic control approach.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While we utilized a novel sustained-release formulation of phenylephrine, we used standard melphalan (aqueous solution) for intratumoral chemotherapeutic injections. Others have shown that a sustained-release liposomal formulation of melphalan enhanced the antitumor effects in preclinical animal models. Our group and others have also published on the beneficial effects of other sustained-release liposomal chemotherapies. , Furthermore, liposomal doxorubicin is an effective and approved drug for different human cancers, including breast and ovarian cancer . Thus, combining sustained-release liposomal formulations of intratumoral chemotherapy may likely have an additional effect on antitumor responses when used in combination with our local dynamic control approach.…”
Section: Discussionmentioning
confidence: 98%
“…67,68 Furthermore, liposomal doxorubicin is an effective and approved drug for different human cancers, including breast and ovarian cancer. 69 Thus, combining sustained-release liposomal formulations of intratumoral chemotherapy may likely have an additional effect on antitumor responses when used in combination with our local dynamic control approach. In addition, although we have focused our investigation of local dynamic control on melanoma, there are other cutaneous or superficially located tumors that may benefit from our approach.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Excitingly, many liposome‐based chemotherapeutic agents have been approved for clinical use by the European Medicines Agency (EMA) and the U.S. Food and Drug Administration (FDA). Examples include PEGylated liposomal DOX (PLD) (brand names: US: Doxil® and Lipodox® (generic Doxil), Europe: Caelyx®), non‐PEGylated liposomal DOX (Myocet®), vincristine sulfate liposome injection (Marq), vincristine sulfate liposome injection (Marqibo®) and irinotecan (IRI) nanoliposome (Onivyde™) 41 . These clinically approved liposome formulations effectively reduce the blood and cardiac toxicity caused by free chemotherapeutic agents in the body and improve the biosafety of chemotherapeutic agents.…”
Section: Organic Nanomaterialsmentioning
confidence: 99%
“…Examples include PEGylated liposomal DOX (PLD) (brand names: US: Doxil ® and Lipodox ® (generic Doxil), Europe: Caelyx ® ), non-PEGylated liposomal DOX (Myocet ® ), vincristine sulfate liposome injection (Marq), vincristine sulfate liposome injection (Marqibo ® ) and irinotecan (IRI) nanoliposome (Onivyde™). 41 These clinically approved liposome formulations effectively reduce the blood and cardiac toxicity caused by free chemotherapeutic agents in the body and improve the biosafety of chemotherapeutic agents. With the improvement of preparation technology, new types of lipid nanoparticles, such as solid lipid nanoparticles (SLNs), lipid polymer hybrid nanoparticles (LPNs) and lipid core nanocapsules (LNCs), have been gradually developed and are expected to overcome the drawbacks of liposome technology.…”
Section: Introductionmentioning
confidence: 99%
“…It is a major component of many chemotherapy treatment regimens in clinical use 2 . In 1995, conventional doxorubicin (CDOX) received FDA approval for the treatment of various cancer types 3 including breast 4 , uterine, ovarian 5 , lung 6 , lymphoma 7 , bladder 8 , and leukemia 7 . However, CDOX, either used alone or in combination with other chemotherapy drugs 9 , induces dose-dependent cardiotoxicity 10 , hematopoietic toxicity, hepatotoxicity, nephrotoxicity, and central neurotoxicity 11,12 .…”
Section: Introductionmentioning
confidence: 99%